2018
DOI: 10.1002/2017jg004275
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Spatial Changes in Trichodesmium Associated With Physicochemical Properties in East China Sea and Southern Yellow Sea

Abstract: Trichodesmium is broadly distributed and occasionally blooms in the East China Sea (ECS) and southern Yellow Sea, where it contributes to local N and C budgets. However, its population structure, spatiotemporal distribution, controlling factors, and N2 fixation remain poorly documented. Here we provide high spatial resolution data sets of Trichodesmium during the four seasons of 2011–2012 using water‐ and net‐collected methods. The net‐collected method captures colonial trichomes of Trichodesmium effectively b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
43
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 83 publications
(323 reference statements)
3
43
1
Order By: Relevance
“…Previous studies have observed high abundance of Trichodesmium in Kuroshio and bifurcation regions (Chen et al, ; Jiang et al, , ; Marumo & Asaoka, ; Shiozaki, Takeda, et al, ; Zhang et al, ). Similarly, high‐density Richelia / Calothrix were observed in/near upstream Kuroshio (Chen et al, ), the Kuroshio Extension (Kitajima et al, ), and the Tsushima Strait affected by Kuroshio branch (Shiozaki et al, ) through fluorescence microscopy.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Previous studies have observed high abundance of Trichodesmium in Kuroshio and bifurcation regions (Chen et al, ; Jiang et al, , ; Marumo & Asaoka, ; Shiozaki, Takeda, et al, ; Zhang et al, ). Similarly, high‐density Richelia / Calothrix were observed in/near upstream Kuroshio (Chen et al, ), the Kuroshio Extension (Kitajima et al, ), and the Tsushima Strait affected by Kuroshio branch (Shiozaki et al, ) through fluorescence microscopy.…”
Section: Introductionmentioning
confidence: 91%
“…Shiozaki et al () found relatively abundant Richelia in Kuroshio from northeastern Taiwan to south of mainland Japan. Several studies have suggested that abundant Trichodesmium can be transported to vast regions by Kuroshio (Jiang et al, ; Marumo & Asaoka, ; Shiozaki, Takeda, et al, ; Zhang et al, ). In this context, we hypothesize that the incursion of Kuroshio may profoundly influence composition and distribution of filamentous diazotrophs in the ECSYS.…”
Section: Introductionmentioning
confidence: 99%
“…This contrast probably suggests that biological fixed nitrogen in the ECS shelf is not mainly produced by diazotroph living in the continental shelf of the ECS but overwhelmingly produced in the Kuroshio water, which are transported to the ECS shelf as Kuroshio intrudes. Consistently, based on the nitrogen budget for the ECS (Zhang et al, ) and the conservative estimation that 20% of the nitrogen in the upwelled Kuroshio water is from nitrogen fixation (Liu et al, ), the biological fixed nitrogen by Kuroshio input to the continental shelf of the ECS are estimated to be 10 (0.30 versus 0.03 × 10 12 g) and 2.6 (0.13 versus 0.05 × 10 12 g) times higher than local N 2 fixation fluxes (Jiang et al, ) during autumn and summer, respectively.…”
Section: Discussionmentioning
confidence: 92%
“…By contrast, our study probably benefited from the relatively small area and the well‐mixed water column. The scattering of δ 15 N with temperature (Figure c) may be caused by additional factors influencing nitrogen fixation rate, such as dissolved phosphorus concentration (Mulholland & Bernhardt, ) and some other nitrogen fixers like the unicellular diazotroph which behave differently with temperature compared to Trichodesmium (Chen et al, ; Jiang et al, ; Moisander et al, ). Although nitrification, a biological oxidation of NH 4 + to NO 3 − via NO 2 − , more strongly correlates with the water temperature than nitrogen fixation (Sugimoto et al, ), it would not contribute to such a negative correlation between δ 15 N of planktonic OM and temperature due to the N depletion in the study area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation